Hypertension, lipids and carbohydrate disorders among women in perimenopause – hormonal and pathophysiological aspects - Mądro, Elżbieta; Małecka-Massalska, Teresa (Polish Journal of Public Health, 2010)
Perimenopause is a transitional period lasting approximately 5 years and preceding final menstrual menses. In other words, it is transition between reproductive age and menopause. It is the period directly before menopause when the first clinical, hormonal and biological symptoms of approaching final menses appear or the first year after menopause. Diseases which may appear during perimenopause are caused by metabolic and hormonal disturbances characteristic for this period. They are: hypertension, lipid and carbohydrate disorders, osteoporosis. The results of last studies give new insight into the role of the adipose tissue. This tissue is the highly hormonally active gland of internal secretion producing a number of biologically active peptides which can have local as well as systemic effects. Main cells adipose are adipocytes which secrete bioactive substances such as: leptin, adiponectin, resistin, visfatin, omentin, adipsin, PAI-1, TNF-alfa, angiotensinogen, interleukin 6, lipoprotein lipase. Abdominal fat and adipose tissue increase are responsible for the development of insulin resistance. There are hormonal mechanisms regulating correlations between adipose and bone tissue. Osteoblasts show expression of receptors for ghrelin, which stimulates their proliferation and differentiation. Effects of ghrelin on bones are not known yet. It was stated that nocturnal ghrelin concentration correlates with BMD (bone mineral density) among women. The article describes the hormonal and pathophysiological aspects of disorders (hypertension, lipid and carbohydrate disorders, osteoporosis), which appear among women in perimenopause.